Unique associations between sports coaches` personality and the coach - athlete working alliance - Schmid, J.; Olsen, M.; Moen, F. (International Journal of Coaching Science, 2020)
The current cross-sectional study explored associations between coaches` personality traits and their perceptions of their working alliances with their athletes. A sample of 107 Norwegian elite coaches participated in the current study by completing an online questionnaire measuring personality (the Big Five inventory-BFI), Grit and the Coach-Athlete Working Alliance Inventory (CAWAI). Hierarchical multiple regression analyses showed that the BFI traits and Grit uniquely explained 38% of the variance in the CAWAI scores, and 31%, 25%, and 33% of the variance in the CAWAI dimensions goal, task and bond, respectively. Extraversion and Grit were significant predictors of CAWAI scores. Furthermore, the results indicated that the different personality traits influenced the three dimensions of the CAWAI in different ways. The results were discussed in light of on several coach-athlete relationship frameworks, and with applied implications and possible future research in mind.